PENGARUH GAYA HIDUP, DEMOGRAFI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN - Suhardi, Suhardi (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2019)
ABSTRACT - Lifestyle change in the demographic structure of society, especially in city of Karawang area who believe that shopping at modern retail outlets add to the prestigue of its own in the social life makes competition in the provision of retail entrepreneurs staples and daily necessities has increased mainly about improved quality of goods and services led to the the level of consumer purchasing decisions.The Purpose of Research are analizing the Effect of life style, demography and product quality toward customer buying desicion partially and simultaneously.This Research is done at alfamart outlet Mitra Usaha CV. Family which located at Jl. Ir. H. Juanda Cikampek Karawang. This Research used 80 respondents determined by purposive sampling technic due to the unlimited population.This reseach uses multiple regression analysis by using three independent variables and one dependent variable.The result of research shows that life style,demography dan product quality proved positive and significant effect to customer buying desicion partially and simultaneously.Therefore, life style, demography and product quality are important factors to increase buying desecion.